Development and validation of HPLC-UV method for the estimation of Bortezomib in human plasma - Bhetanabotla Chandramowli; Bigala B Rajkamal (International Journal of Pharmacy and Analytical Research, 2022)
A Simple, rapid, selective and sensitive HPLC method was developed and validated for the determination of Bortezomib from human plasma. The drug was extracted with ethyl acetate. Bortezomib was measured in plasma using a validated a HPLC method with UV detector at 270nm chromatographic peaks were separated on 5µm intensil, C18 column (4.6x250mmx5µm) using a mixture of water -acetonitrile-formic acid (71: 28: 1, v/v/v ) as mobile phase at a flow rate of 1 ml/min, pH 6 was adjusted with triethyllamime. The chromatograms showed good resolution and no interference from plasma. The retention time of Bortezomib and internal standard were approximately 5.9±0.05 min and 10.19± 0.03 min respectively. The mean recovery from human plasma was found to be above 88%. The method was linear over the concentration range of 0.3 to 20 µg/ml with coefficient of correlation (r2) 0.998. Both intraday and interday accuracy and precision data showed good reproducibility. This method was successfully applied to pharmacokinetics studies.